2018
DOI: 10.1158/1078-0432.ccr-17-3262
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Elastography and Its Association with Collagen and the Tumor Microenvironment

Abstract: The tumor microenvironment presents with altered extracellular matrix (ECM) and stroma composition, which may affect treatment efficacy and contribute to tissue stiffness. Ultrasound (US) elastography can visualize and quantify tissue stiffness noninvasively. However, the contributions of ECM and stromal components to stiffness are poorly understood. We therefore set out to quantify ECM and stroma density and their relation to tumor stiffness. A modified clinical ultrasound system was used to measure tumor sti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
83
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 44 publications
10
83
1
Order By: Relevance
“…Furthermore, examination of primary tumors by fluorescence and second harmonic generation (SHG) microscopy revealed that WISP1 colocalizes with linear collagen fibers ( Fig 4C). Moreover, consistent with a role for fibrillar collagen in increasing tumor stiffness (Levental et al, 2009;Riegler et al, 2018), 4T1-Wisp1 tumors are on average stiffer than 4T1-EV tumors ( Fig 4G). Moreover, consistent with a role for fibrillar collagen in increasing tumor stiffness (Levental et al, 2009;Riegler et al, 2018), 4T1-Wisp1 tumors are on average stiffer than 4T1-EV tumors ( Fig 4G).…”
Section: Wisp1 Remodels Collagen Architecture In Vivo and Promotes Mesupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, examination of primary tumors by fluorescence and second harmonic generation (SHG) microscopy revealed that WISP1 colocalizes with linear collagen fibers ( Fig 4C). Moreover, consistent with a role for fibrillar collagen in increasing tumor stiffness (Levental et al, 2009;Riegler et al, 2018), 4T1-Wisp1 tumors are on average stiffer than 4T1-EV tumors ( Fig 4G). Moreover, consistent with a role for fibrillar collagen in increasing tumor stiffness (Levental et al, 2009;Riegler et al, 2018), 4T1-Wisp1 tumors are on average stiffer than 4T1-EV tumors ( Fig 4G).…”
Section: Wisp1 Remodels Collagen Architecture In Vivo and Promotes Mesupporting
confidence: 76%
“…Importantly, Wisp1 overexpression results in an increase in the frequency and average width of linear collagen fibers in primary tumors ( Fig 4D-F) but does not affect total type I collagen deposition (Fig EV5A and B). Moreover, consistent with a role for fibrillar collagen in increasing tumor stiffness (Levental et al, 2009;Riegler et al, 2018), 4T1-Wisp1 tumors are on average stiffer than 4T1-EV tumors ( Fig 4G). Taken together, these results suggest that, as observed in vitro (Figs 2D and E, and EV2O and Q), WISP1 promotes the linearization of type I collagen without affecting its total amount.…”
Section: Wisp1 Remodels Collagen Architecture In Vivo and Promotes Mesupporting
confidence: 76%
“…An important feature of fibrotic tumors is their considerable higher stiffness compared to their neighboring healthy tissues which is highly correlated with cancer progression and metastasis, particularly in breast, colorectal, liver and pancreatic tumors (22,23). The use of non-invasive imaging techniques such as shear wave elastography (SWE) and magnetic resonance elastography (MRE), designed to monitor stiffness of any given tissue, allow an accurate diagnostic and characterization of malignant lesions in vivo (24). The extensive remodeling of the stromal components increasing tumor stiffness can mechanically activate intracellular signaling 5 pathways that promote tumor progression and at the same time can dampen T cell functions including migration and infiltration into tumor islets (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the tumor mechanical properties were averaged over the entire tumor, whereas tumors are known to be heterogeneous . In the future, necrotic areas may be excluded from analysis, for instance, by concomitantly measuring the local perfusion rate and adopting a minimum threshold of perfusion, as recently proposed . Reference histopathological values were not available for this study, but in the future stained sections could also be prepared and compared with the in vivo images to provide a better understanding of the nature of the various tumor subzones identified at MRI.…”
Section: Discussionmentioning
confidence: 99%